Knowledge of hypertension among the staff of University of Ibadan, Nigeria (International Journal of Medicine and Medical Sciences, 2019)
Several lines of evidence have suggested that hypertension and its related complications are major health problems not only in Nigeria but the entire world. Thus, this study examined the awareness about the risk factors and complications associated with hypertension at the University of Ibadan, Nigeria. Questionnaire instrument was used to collect data from a randomly selected 556 subjects selected across faculties, departments and sectional units of the University. The descriptive statistics showed that some members of staff demonstrated a relatively high level of knowledge about the complications associated with hypertension but knowledge about the risk factors and attitude towards the illness was still low. However, level of education significantly influences awareness of complications (at 0.05) and knowledge of risk factors (at 0.05). On-job screening and educative programmes are fundamental ways to improve knowledge about hypertension at the work-place.